Effect of Sulfur Content in Wetar Pyrite Waste on the Formation Process of Sulfuric Acid Products at AIM Project Morowali - Yulian Putra, Rizky Wira; Totok Eka Suharto; Erna Astuti (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2025)
Pyrite ore is a sulfide mineral commonly found in mining operations, and has the potential to be converted into valuable chemical products. The substantial quantity of high-quality pyrite ore waste generated by the Wetar Copper Mine is non-reusable, potentially causing environmental issues upon exposure to air. To mitigate potential environmental contamination at the Wetar Copper Mine, the AIM Project was initiated to process high-quality pyrite ore waste into sulfuric acid. This study aims to determine the effect of sulfur content, measured as a percentage of sulfur recovery, on the conversion of SO2 gas to SO3. Concentrate and calcine samples with particle size variations of 100, 120, 160 and 200 mesh were analyzed on a Carbon Sulfur Analyzer (CSA) with combustion temperature variations of 1100, 1150, 1200 and 1250˚C to determine sulfur content as a reference for the potential amount of SO2 to SO3 conversion in sulfuric acid formation. The results showed that the conversion of SO₂ gas to SO₃ increased with increasing particle size, with a particle size of 200 mesh yielding an optimum sulfur gas conversion percentage of 4.12%. At the same conditions, a maximum sulfur recovery rate of 96.66% was obtained from an average particle size of 200 mesh.